2003
DOI: 10.4319/lo.2003.48.1_part_2.0456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epiphyte load on optical properties and photosynthetic potential of the seagrasses Thalassia testudinum Banks ex König and Zostera marina L.

Abstract: The biomass and optical properties of seagrass leaf epiphytes were measured to evaluate their potential impact on the photosynthetic performance of the seagrasses Thalassia testudinum Banks ex König (turtlegrass) and Zostera marina L. (eelgrass). Turtlegrass was obtained from oligotrophic waters near Lee Stocking Island, Bahamas; eelgrass was collected from a eutrophic environment in Monterey Bay, California. Leaf-epiphyte loads were characterized visually and quantified using measurements of their phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 38 publications
(43 reference statements)
3
48
0
Order By: Relevance
“…Light availability on the surface of the leaves of Z. marina covered by epiphytes was dramatically decreased compared to leaves without epiphytes in agreement with previous studies (Drake et al, 2003;Pedersen et al, 2014). Effectively, this means that a higher downwelling photon irradiance is needed to meet the compensation irradiance for the epiphyte covered leaf (Figure 6).…”
Section: Light Microenvironment and Shoot Photosynthesissupporting
confidence: 78%
“…Light availability on the surface of the leaves of Z. marina covered by epiphytes was dramatically decreased compared to leaves without epiphytes in agreement with previous studies (Drake et al, 2003;Pedersen et al, 2014). Effectively, this means that a higher downwelling photon irradiance is needed to meet the compensation irradiance for the epiphyte covered leaf (Figure 6).…”
Section: Light Microenvironment and Shoot Photosynthesissupporting
confidence: 78%
“…The temporal effect of canopy movement on PAR absorptance and bidirectional reflectance could then be quantified and may be significant, since the distribution of leaf orientations has previously been demonstrated as a potentially important factor (Zimmerman 2003). The effect of leaf epiphytes has also been neglected here (Cebriá n et al 1999;Drake et al 2003), since epiphyte load at the six sites was low, but this could be incorporated in future work. Temporal light fluctuations due to wave focusing are an important feature of shallow water environments.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the success of requirement (1) can also be affected by epiphytic loading, which can remarkably change the reflectance of eelgrass. Studies have shown that heavy epiphyte loads can absorb up to 63% of incident light in the peak chlorophyll absorption bands, leading to greater reflectance slopes at 440 nm and 680 nm than at 550 nm [25]. Reflectance in the 575-630 nm region is markedly increased [26] while green light is physically blocked by non-photosynthetic material accumulation [25] and absorbed by non-chlorophyte epiphytes [27].…”
mentioning
confidence: 99%
“…Studies have shown that heavy epiphyte loads can absorb up to 63% of incident light in the peak chlorophyll absorption bands, leading to greater reflectance slopes at 440 nm and 680 nm than at 550 nm [25]. Reflectance in the 575-630 nm region is markedly increased [26] while green light is physically blocked by non-photosynthetic material accumulation [25] and absorbed by non-chlorophyte epiphytes [27]. These effects lead to a flattening of the eelgrass spectral signature and increased variability in green reflectance values [26,28].…”
mentioning
confidence: 99%